Vlijanie processov globalizaciina razvitie sportivnyh igr - Sushko, R. (Science in Olympic Sport, 2018)
Objective. To analyze the current trends in the development of team sports taking into account the influence of globalization processes in high performance sport. Methods. Analysis and generalization of scientific and methodological literature and data on the Internet; pedagogical obser-vations; and expert assessments. Results. The features of the evolution of team sports in the context of globalization of high performance sport are reviewed and examined based on the infl uence of the following factors: migration of the athletes and their concentration in national and international leagues, and sports training centers; professionalization and commercialization of national and international official competitions; politicization of official international competitions; socialization of athletes and informatization of society. The current trends in the development of team sports are identified on the basis of the data of expert assessments taking into account the influence of globalization processes in high performance sport. Possible ways are outlined to address the topical issues of the development of team sports in Ukraine and to overcome the critical situation of non-compliance with the international level combined with the existing high potential and victorious traditions of the past taking into account the knowledge accumulated by experts and the need for an appropriate interpretation of the existing experience of foreign countries. Conclusion. Increasing trends in popularity of team sports are revealed and signifi cant infl uence of processes of globalization are emphasized on the basis of its leading factors. The analysis of the characteristics of the sports globalization and the results of the expert assessment make it possible to conclude that modern professional sport has undergone drastic changes. Its further progressive development is possible only taking into account the recognition of the existing influence of global factors and requires the modified approaches to build a multiyear training system, the appropriate scientific justifi cation, and legal support provided by the governmental bodies. This will allow to develop sound practical technologies for creating educational-training and competitive processes in order to overcome the existing imbalance in team sports between winning traditions of the past and disappointing results at the current time.